2008
DOI: 10.1021/ol801878f
|View full text |Cite
|
Sign up to set email alerts
|

Highly Diastereoselective Addition of Lithio Vinyl Sulfoxides to N-Sulfinimines: An Entry to Enantiopure 3-Sulfinyl-2,5-cis-dihydropyrroles

Abstract: The addition of enantiopure alpha-metalated vinyl and dienyl sulfoxides to enantiomerically pure N-sulfinimines takes place with high diastereoselectivity primarily directed by the N-sulfinimine sulfur. The resulting allylic amines have been further transformed into highly functionalized 3-sulfinyl and 3-sulfonyl 2,5- cis-dihydropyrroles by reaction with electrophiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…25-2.35 (m, 4H,C H 2 piperidine + H-1), 2.59 (m, 2H,C H 2 piperidine), 4. 15 (m, 1H,H -2), 5.13 (d, 1H, J = 6.1 5. 61 (ddd, 1H, J = 15.3, 6.1, 1.1 Hz, H-3), 5.81 (ddd,1H,J = 15.4,6.1,1.0 Hz,1H,P h),4H,Ph); 13 CNMR (CDCl 3 ,1 25 MHz): d = 13.7 (3 x CH 2 nBu), 13.8 (3 x CH 3 nBu), 24.1 (CH 2 piperidine), 25.4 (3 x CH 2 nBu), 25.9 (2 x CH 2 piperidine), 26.6 (3 x CH 2 nBu), 54.5 (2 x CH 2 piperidine), 64.4 (C-1), 66.7 (C-2), 74.8 (C-5), 126.1 (2 x Ph), 127.0 (Ph), 128.1 (2 x Ph), 129.7 (C-3), 135.2 (C-4), 143. 8 (Ph).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…25-2.35 (m, 4H,C H 2 piperidine + H-1), 2.59 (m, 2H,C H 2 piperidine), 4. 15 (m, 1H,H -2), 5.13 (d, 1H, J = 6.1 5. 61 (ddd, 1H, J = 15.3, 6.1, 1.1 Hz, H-3), 5.81 (ddd,1H,J = 15.4,6.1,1.0 Hz,1H,P h),4H,Ph); 13 CNMR (CDCl 3 ,1 25 MHz): d = 13.7 (3 x CH 2 nBu), 13.8 (3 x CH 3 nBu), 24.1 (CH 2 piperidine), 25.4 (3 x CH 2 nBu), 25.9 (2 x CH 2 piperidine), 26.6 (3 x CH 2 nBu), 54.5 (2 x CH 2 piperidine), 64.4 (C-1), 66.7 (C-2), 74.8 (C-5), 126.1 (2 x Ph), 127.0 (Ph), 128.1 (2 x Ph), 129.7 (C-3), 135.2 (C-4), 143. 8 (Ph).…”
Section: Methodsmentioning
confidence: 99%
“…In connection with our interest in the development of stereocontrolled methodologies using enantiopure sulfinyl auxiliaries, [5] and our interesti na cyclic stereocontrol,w ec onsidered that functionalized sulfinyl dienes A could undergo ac onjugate addition of an appropriate nucleophile, [6] to generate intermediate B (Scheme 1b). Subsequent protonation, either to alkenyl sulfoxides B' with ensuing isomerization, or to allylic sulfoxides C,c ontrolled by the preexisting contiguous chiral center,w ould eventually trigger the highly selective [ 2,3]-sigmatropic rearrangementt op roduce unsaturated 1,4-diol or 1,4-aminoalcohold erivatives D,a fter sulfenate cleavage by excess nucleophile acting as thiophile.…”
Section: Introductionmentioning
confidence: 99%
“…[115][116][117] Viso et al demonstrated stereoselective synthesis of enantiopure dihydropyrroles where TBATB plays the dual role of brominating agent as well as an acid catalyst. 118,119 Here, the double bond functionality first undergoes bromination to form the dibromo intermediate in the presence of the brominating reagent TBATB. Next TBATB catalyses the reaction to undergo base induced bromo-cyclization (Scheme 35).…”
Section: Synthesis Of Enantiopure Dihydropyrroles From a Sulfinylsulf...mentioning
confidence: 99%
“…Moreover, Satoh and coworkers [66][67][68] prepared different bioactive products from the 1-chlorovinyl ptolylsulfoxide, resulting in the addition of α-chlorosulfinyl carbanions to aldehydes and further elimination with MsCl. In 2008, Viso and Fernández de la Pradilla [77,78] published the first addition of sulfinylated vinyl carbanions to N-sulfinyl-imines. He has used the sulfinyl-allylic alcohols obtained in the addition of lithium-vinylsulfoxides to aldehydes in oxidation studies [69][70][71][72], isomerization reactions [73], and Overman [74], Claisen [75], and sulfoxide-sulfenate [76] rearrangements.…”
Section: Vinylic Carbanionsmentioning
confidence: 99%